1969
DOI: 10.1088/0022-3727/2/1/422
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of secondary processes in the streamer breakdown of gases

Abstract: Mechanisms which may act as secondary processes in the streamer breakdown of isotropic gases and air are considered. In the case of air it is shown that mechanisms connected with the collisions of excited oxygen molecules with groundstate nitrogen and oxygen molecules play the primary role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1970
1970
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The charged particle production by this reaction occurs by collision of an excited atom Ar * with an atom in the ground state. The reaction occurs if the excitation energy E * of an atom Ar * is larger than the difference between the ionization potential of the Ar atom I = 15.76 eV and the dissociation energy E d = 1.23 eV of molecular ion Ar + 2[26] E * > I − E d .…”
mentioning
confidence: 99%
“…The charged particle production by this reaction occurs by collision of an excited atom Ar * with an atom in the ground state. The reaction occurs if the excitation energy E * of an atom Ar * is larger than the difference between the ionization potential of the Ar atom I = 15.76 eV and the dissociation energy E d = 1.23 eV of molecular ion Ar + 2[26] E * > I − E d .…”
mentioning
confidence: 99%
“…The data by Penney and Hummert also have a part with a smaller absorption coefficient, though the intensity is far lower. An account for this part may be made assuming a reaction Nz+Nz*-t N4++e (Lozansky 1969), N2* denoting the excited neutral molecule. Since the dissociation energy of NqL into Nz +Nz+ is about 0-069 eV (Flannery et aZ1973), photons with energies slightly lower than the first ionization energy may serve for the reaction (Lozansky 1969).…”
Section: W+=(mentioning
confidence: 99%
“…An account for this part may be made assuming a reaction Nz+Nz*-t N4++e (Lozansky 1969), N2* denoting the excited neutral molecule. Since the dissociation energy of NqL into Nz +Nz+ is about 0-069 eV (Flannery et aZ1973), photons with energies slightly lower than the first ionization energy may serve for the reaction (Lozansky 1969). These photons may have absorption coefficients around an order of magnitude smaller than the value above (Cook and Metzger 1964).…”
Section: W+=(mentioning
confidence: 99%
“…Also photodetachment can occur without the existence of highly excited states of nitrogen molecules which must then decay directly to the ground state in order to produce the radiation essential for photoionization. Lozansky (1969) has considered photoionization as a possible process involved in the streamer breakdown of uniform field gaps in air. He concluded that in this case photoionization could not be important because the large absorption coefficient of the necessary high energy photons would result in them being absorbed before they could move sufficiently 1220 F. D. A .…”
Section: Introductionmentioning
confidence: 99%